2020
DOI: 10.1097/md.0000000000022511
|View full text |Cite
|
Sign up to set email alerts
|

Adult granulosa cell tumors of bilateral ovaries with pure cystic presentation

Abstract: Rationale: Granulosa cell tumors (GCTs) are rare, hormonally active sex cord-stromal tumors that generally present as solid unilateral ovarian lesions. It's quite uncommon that they present as pure bilateral ovarian cysts. Histopathology remains the gold standard for making a diagnosis of GCTs. However, as the differential diagnosis is difficult, cystic GCTs are frequently misdiagnosed as benign or other cystic tumors either prior to surgery or during pathologic diagnosis. Accordingly, herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Immunohistochemistry revealed that granulosa cells displayed stable expression of inhibin-α, WT-1, and CD56. Based on the combination of inhibin-α, WT-1, and positive CD56, pathologists can always be confident in the diagnosis of GCT [11] . In the above case, the epithelial cells of the ovarian tumors were also positive for inhibin-α, WT-1, and CD56.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Immunohistochemistry revealed that granulosa cells displayed stable expression of inhibin-α, WT-1, and CD56. Based on the combination of inhibin-α, WT-1, and positive CD56, pathologists can always be confident in the diagnosis of GCT [11] . In the above case, the epithelial cells of the ovarian tumors were also positive for inhibin-α, WT-1, and CD56.…”
Section: Discussionmentioning
confidence: 87%
“…Based on the combination of inhibin-α, WT-1, and positive CD56, pathologists can always be confident in the diagnosis of GCT. [ 11 ] In the above case, the epithelial cells of the ovarian tumors were also positive for inhibin-α, WT-1, and CD56. Surgical staging is the most important indicator of prognosis, recurrence, and treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Although granulosa cell tumors are hormonally active tumors, patients often present with nonspecific symptoms; currently there are no diagnostic imaging criteria for these tumors [ 6 ]. Differential diagnosis includes hypercalcemic small cell carcinoma, adenocarcinoma, ovarian thecoma and carcinoid tumors [ 4 , 7 ]. Unlike the juvenile type, adult granulosa cell tumor of the ovary has a characteristic coffee bean grooved and uniform nuclei in 30–60% of cases and often have an immunocytochemistry positive for inhibin [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unilocular cystic AGCTs are rare, but have been reported (8). In these cases, the presence of nuclear grooves and variable architectural patterns have been documented.…”
Section: Discussionmentioning
confidence: 99%